The Relationship Between Family Support And The Attitudes Of Partworld Mothers In Exclusive Breastfeeding At The Hj Clinic. Tarpianie Amd. Keb Prambon Sidoarjo - Vidia Atika Manggiasih; Retno Palupi Yonni Siwi; Erma Retnaningtyas; Tarpianie (Journal of Health Science Community, 2024)
Mother's Milk (ASI) is the best and most suitable food for babies to ensure the growth of babies into human quality. The substances contained in breast milk contain almost all the nutrients needed by babies with concentrations that suit the needs of the baby. (MOH RI, 2014). Based on preliminary studies conducted by researchers at Clinic Hj. Tapianie Prambon Sidoarjo in January 2020 from 15 respondents showed that the attitude of the mother in giving exclusive breast milk is very good this is because of the large amount of family support in motivating mothers to want to breastfeed exclusively. The purpose of this study was to determine the Relationship Between Family Support and Attitude of Postpartum Mother in Giving Exclusive Asi at Clinic Hj. Tarpianie Prambon Sidoarjo Year 2020. The design of this study included a cross sectional analytic study with a survey approach. The population in this study were all postpartum mothers in Clinic Hj. Tarpianie Amd.Keb Prambon Sidoarjo Year 2020, the sample in this study was taken with a non-probability sampling technique by means of accidental sampling, amounting to 31 respondents. The independent variable in this study is family support with an ordinal scale and the dependent variable is the attitude in exclusive breastfeeding with an ordinal data scale. This research was conducted from January to July 2020 in the Class of Pregnant Women at Clinic Hj. Tarpianie, Amd. Keb Prambon Sidoarjo using a questionnaire measuring instrument that was tested with a validity and reliability test. In collecting data from respondents the next step taken by researchers is data processing by editing, coding, scoring, tabulating, data entry, and cleaning. Data analysis in this study used the Spearman rank test. From the Spearman rank test results following the normal distribution with a significant level (α = 0.05), it was found that p value <α or 0.001 <0.05 which means that H0 is rejected and H1 is accepted. The conclusion is that there is a relationship between family support and mother's attitude in exclusive breastfeeding. The form of husband's support can be shown by the husband through daily activities, for example giving information to the mother about the importance of exclusive breastfeeding to the baby or taking the mother to a health service to find information. If a mother benefits from all her husband's support, then a mother has received a positive stimulus to change her attitude to be positive.